Masjid Kampus sebagai Ruang Pembentukan Karakter Mahasiswa Muslim: Analisis Sosiokultural Mentoring Islam di Telkom University - Ahmad Sukandar; Endang Komara; Asdianur Hadi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Amid the accelerating rhythm of digital culture, academic competition, and the changing patterns of student life in higher education, the formation of Muslim student character has become an increasingly urgent concern. A campus mosque can no longer be viewed merely as a place of worship; it must also be understood as a strategic nonformal Islamic educational space that nurtures spirituality, morality, social awareness, and student identity in a more contextual way. This study aims to analyze the role of the campus mosque as a space for shaping Muslim student character through the Islamic mentoring program at Masjid Syamsul Ulum, Telkom University. This research employs a descriptive qualitative approach based on document study and thematic analysis of scholarly articles, mentoring program documents, and relevant works on campus mosques, religious moderation, and student character education. The findings show that the mentoring program at Masjid Syamsul Ulum is systematically designed through a clear structure, curriculum, methods, evaluation tools, and mentor regeneration, all of which are integrated with the institutional values of Harmony, Excellence, and Integrity. Socioculturally, the program functions not only as a medium for religious instruction but also as a process of value internalization, habituation of religious practice, strengthening of moderation, and construction of Muslim student identity within a technology-oriented university environment. This study proposes a conceptual understanding that the campus mosque can serve as a strategic space for shaping Muslim students who are religious, moderate, collaborative, and adaptive in the digital era.